1999
DOI: 10.1590/s0100-204x1999001000006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of arcelin protein on the biology of Zabrotes subfasciatus (Boheman 1833), in dry beans

Abstract: RESUMO -A arcelina é uma proteína encontrada em feijões silvestres (Phaseolus vulgaris) e que confere resistência ao caruncho-do-feijão, Zabrotes subfasciatus (Boheman 1833) (Coleoptera: Bruchidae). Estudos foram conduzidos com o objetivo de conhecer o efeito de quatro alelos da proteína arcelina (Arc1, Arc2, Arc3 e Arc4), na biologia de Z. subfasciatus. O experimento foi conduzido no laboratório da Embrapa-Centro Nacional de Pesquisa de Arroz e Feijão, no município de Santo Antônio de Goiás, GO, em condições … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 8 publications
(4 reference statements)
0
3
0
Order By: Relevance
“…Arcelin is found in resistant wild varieties but is absent in many susceptible commercial and wild varieties (Romero Andreas et al 1986;Cardona et al 1990;Blair et al 2010;Zaugg et al 2013). Based on previous studies, arcelin, found in several wild genotypes, is associated with resistance in common beans (Osborn et al 1986(Osborn et al , 1988Romero Andreas et al 1986;Cardona et al 1989Cardona et al , 1990Minney et al 1990;Velten et al 2007), and types 1, 2, and 5 are the most resistant against bruchids (Barbosa et al 1999;Baldin and Lara 2008;Sakthivelkumar et al 2013). Arcelin prolongs immature development of A. obtectus by 15% (Schmale et al 2002) and acts as a growth inhibitor on first instar larvae.…”
Section: Introductionmentioning
confidence: 99%
“…Arcelin is found in resistant wild varieties but is absent in many susceptible commercial and wild varieties (Romero Andreas et al 1986;Cardona et al 1990;Blair et al 2010;Zaugg et al 2013). Based on previous studies, arcelin, found in several wild genotypes, is associated with resistance in common beans (Osborn et al 1986(Osborn et al , 1988Romero Andreas et al 1986;Cardona et al 1989Cardona et al , 1990Minney et al 1990;Velten et al 2007), and types 1, 2, and 5 are the most resistant against bruchids (Barbosa et al 1999;Baldin and Lara 2008;Sakthivelkumar et al 2013). Arcelin prolongs immature development of A. obtectus by 15% (Schmale et al 2002) and acts as a growth inhibitor on first instar larvae.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most famous and important defense proteins is arcelin due to its insecticidal properties, and in particular, because of its inhibitory activity on larval development of pests of stored grains (Cardona et al, 1990;Janarthanan and Suresh, 2003;Janarthanan et al, 2008). Resistance in bean genotypes to weevils caused by the presence of arcelin has been found by several authors (Osborn et al, 1988;Wanderley et al, 1997;Barbosa et al, 1999;Miranda et al, 2002;Mazzonetto and Vendramim, 2002). Another important group of defense proteins that has been reported as the cause of antibiosis resistance to weevils are trypsin inhibitors and vicilin globulins (Gatehouse et al, 1979;Macedo et al, 1993;Sales et al, 2005).…”
Section: Introductionmentioning
confidence: 98%
“…So far, six arcelin variants have been isolated and biochemically characterized (Osborn et al, 1986;Lioi & Bollini, 1989;Santino et al, 1991). The main target insect for arcelin is Zabrotes subfasciatus (Barbosa et al, 1999). In contrast, effects of arcelin against A. obtectus are less complete.…”
Section: Introductionmentioning
confidence: 99%